Effects of Flag Leaf and Number of Vegetative Ramets on Sexual Reproductive Performance in the Clonal Grass Leymus chinensis - Guo, Jian; Li, Haiyan; Zhou, Chan; Yang, Yunfei (Frontiers in Plant Science, 2020)
Sexual reproduction is vital for population adaptation in clonal plants. The flag leaf is considered to be the primary contributor to sexual reproduction in cereal crops, and there is no unified conclusion on the effect of the number of vegetative ramets on grain yield. However, what effects of the flag leaf and the number of vegetative ramets on sexual reproductive performance of clonal grasses are largely unknown. To test this, under field natural conditions, we grew the rhizomatous grass Leymus chinensis in a homogeneous environment and conducted studies concerning the growth, reproduction and physiology of reproductive ramets in clonal populations. We measured the growth characteristics of different aged leaves, dynamically measured the net photosynthetic rate of different aged leaves and organ biomass, measured the sexual reproductive characteristics of reproductive ramets that had different numbers of connecting vegetative ramets, and performed isotope (15N) labeling of ramet pairs at the seed-filling stage. In L. chinensis clonal populations, from the heading stage, the photosynthetic contribution of the functional leaves to seed production was much greater than that of the flag leaf; the photosynthetic capacity of both the functional leaves and the flag leaf all gradually declined. Vegetative ramets translocated their own resources to the connected reproductive ramets, and a large proportion of translocated resources were allocated to the leaf and stem to sustain life activities; increase in the number of connecting vegetative ramets increased floret number, seed number, seed-setting rate, inflorescence biomass, seed biomass and reproductive allocation of reproductive ramets, and these parameters significantly and positively correlated with the biomass of connecting vegetative ramets. We conclude that the functional leaf rather than the flag leaf of L. chinensis is the primary contributor to seed production. Reproductive ramets adopt a strategy of growth first and reproductions later to allocate the translocated resources between the organs, but vegetative ramets are very advantageous for sexual reproduction under the tillering node connection form in L. chinensis. Overall, our study implies that vegetative ramets not only play an important role in the spatial expansion but also in the sexual reproduction of clonal plant populations.